2021
DOI: 10.4103/ijo.ijo_1917_20
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the pediatric retina

Abstract: Recent decade has seen a shift in the causes of childhood blinding diseases from anterior segment to retinal disease in both developed and developing countries. The common retinal disorders are retinopathy of prematurity and vitreoretinal infections in neonates, congenital anomalies in infants, and vascular retinopathies including type 1 diabetes, tumors, and inherited retinal diseases in children (up to 12 years). Retinal imaging helps in diagnosis, management, follow up and prognostication in all these disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…Hsu et al also found using OCTA that age, race and axial length are factors that influence quantitative parameters when imaging the pediatric perifoveal vasculature [ 15 ]. Image optimization is needed in pediatric eyes due to increasing axial length with age, evolving refractive status, steeper cornea and greater astigmatism in the first 6 months of life [ 9 ]. Moving forward, more work is needed to validate different portable OCT and OCTA over populations of various ethnicities.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsu et al also found using OCTA that age, race and axial length are factors that influence quantitative parameters when imaging the pediatric perifoveal vasculature [ 15 ]. Image optimization is needed in pediatric eyes due to increasing axial length with age, evolving refractive status, steeper cornea and greater astigmatism in the first 6 months of life [ 9 ]. Moving forward, more work is needed to validate different portable OCT and OCTA over populations of various ethnicities.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…B scan ultrasonography is a non-invasive imaging modality that detects large retinal or choroidal lesions [ 9 ]. Compared with OCT, B scan ultrasonography has a much lower resolution and OCT is much more precise in detecting pre-retinal, intra-retinal and subretinal lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Some measurements obtained, mostly from the fovea, could potentially be used to screen for conditions like ROP (132). HH-OCT-A in specific is extremely useful in cases of CNV in children, such as ROP, retinal dystrophies, inflammatory disorders, trauma or cases of unexplained visual loss (134)(135)(136). Ocular measurements, specifically RNFL thickness, have been shown to be associated with systemic health conditions in infants (low birth weight, sepsis, and necrotizing enterocolitis) (137).…”
Section: Handheld Optical Coherence Tomographymentioning
confidence: 99%
“…The added advantages of its use in children include lack of ionising radiation, reduced requirement of sedation or general anaesthesia and a quick comprehensive evaluation in an often apprehensive child. 1 Detailed crosssectional anatomy of the entire globe and surrounding orbital structures can be visualised using conventional ultrasound transducers. The cornea and anterior chamber structures of the eye rarely require ultrasound as they are amenable to clinical inspection, slit lamp and ophthalmoscopic examination.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound examination is rapid, cost‐effective, easily available and enables dynamic study of the orbital structures. The added advantages of its use in children include lack of ionising radiation, reduced requirement of sedation or general anaesthesia and a quick comprehensive evaluation in an often apprehensive child 1 . Detailed cross‐sectional anatomy of the entire globe and surrounding orbital structures can be visualised using conventional ultrasound transducers.…”
Section: Introductionmentioning
confidence: 99%